Parental migrant status and health inequalities at birth: The role of immigrant educational selectivity. (June 2021) - Florian, Sandra; Ichou, Mathieu; Panico, Lidia
Abstract: Immigrants tend to exhibit better health than natives despite immigrants' more disadvantaged socioeconomic status. This paradox has often been attributed to immigrants' pre-migration selectivity. However, most empirical studies investigating the role of selectivity have focused on adult health; less attention has been paid to children's birth outcomes outside the U.S. context. Using data from the Etude Longitudinale Française depuis l'Enfance (ELFE), a nationally representative sample of over 18000 births in France in 2011, we investigate the role of immigrant parents' educational selectivity in shaping four birth outcomes: birthweight, low birthweight, prematurity, and being born small for gestational age. Results from linear and logistic regressions confirm a health advantage for children of immigrants compared to natives despite lower parental socioeconomic status, mainly among children of Middle Eastern and North African parents. Immigrant parents' positive pre-migration educational selectivity explains most of this health advantage, predominantly among children with two immigrant parents. Further, mediation analyses indicate that the effect of educational selectivity is partially mediated by parental health behaviors, particularly smoking during pregnancy. Furthermore, analyses suggest that selectivity improves birth outcomes only for children of recent arrivals, with less than five years of residence in France. The beneficial effect of selectivity declines with length of residence, suggesting that a process of "unhealthy assimilation, " coupled with the cumulative exposure to health risks and disadvantaged living conditions, may lead to the erosion of the protective effect of immigrant selectivity. Highlights: Despite lower SES, immigrants' children are in better health at birth in France. Parents' pre-migration educational selectivity explains most of this paradox. Benefits of selectivity are partly mediated by migrants' better health behaviors. The health benefits of educational selectivity decrease with length of residence.